Present-day Value Orientations through the Prism of Actual Word Compatibility - Marinova, Elena (Przegląd Wschodnioeuropejski, 2018)
The phenomenon of actual word compatibility appearing in current written speech is considered. The term actual word compatibility is introduced into scientific use to denote new or relatively new compatibility of the words breaking their usual syntagmatic connections and identifying changes in people’s value orientations. Analyzing the compatibility of the adjectives with positive or negative meaning in sintagmas like zdorovyj cynizm (‘healthy cynicism’), razumnaja agressija (‘reasonable aggression’), nezdorovaja dobrota (‘harmful kindness’), etc. the author comes to the conclusion that in the present-day perception there are some value orientations not typical of traditional culture. One of them is aggressive cult of force. The study is performed in the framework of language dynamic description on the material of the texts related to several professional communities (lawyers, psychologists, business coaches) and comments on them on the websites, etc. One of the methods applied is the analysis of potential word compatibility.